Legal consideratios in developing and implementing the 2018 draft intergrated resources plan (IRP): a case study of the nuclear sector - Kenny, Fadeelah (Department of Electrical Engineering, 2020)
The 2018 Draft Integrated Resource Plan (IRP) published by the Department of Energy (DoE) of South Africa informs the government’s electricity demand projections until 2050. They are published under the authority of the Electricity Regulation Act (ERA) of 2006. The Electricity Regulations on New Generation Capacity of 2009 stems from the ERA. The draft IRP must, however, be seen in the context of previous IRPs, and policy considerations outlined in Chapter 2. The draft IRP 2018 sets out to estimate the generating capacity requirements and allocates how much of each energy technology will be commissioned during the projection window. The rollout of the nuclear component of the IRP has had many challenges since the first original IRP was published in 2010. Apart from varied policy jockeying regarding the various energy sectors in South Africa (SA), court cases and other factors, allegations of corruption and maladministration have caused major delays in the envisaged nuclear rollout. This dissertation identifies the legal measures that Eskom as the licence holder and various government entities need to comply with to successfully roll out the nuclear component of the draft IRP 2018. It will describe the applicable legislation, processes and illustrative court cases. In so doing the work will provide guidance on the steps to follow to ensure that the nuclear rollout complies with the legal and policy framework of SA and gets delivered successfully and efficiently. The latest draft IRP 2018 which was published for public comments in the Government Gazette dramatically revises the forecast for SA’s energy demand downwards from a projection of 525 Terawatt hours (TWh) of power in 2050 to 430 TWh for the most optimistic ‘high’ scenario. This revision is the main reason the new IRP no longer calls for massive new coal plants and has relegated nuclear to specific scenarios instead of the ‘base case’. The carbon budget (IRP6) and carbon budget plus market-linked gas price (IRP7) scenarios commission nuclear capacity of 4200 megawatts (MW) and 5600 MW respectively for the period 2031-2040. IRP 6 and 7 have 6 per cent (6.3GW) and 7 per cent (7.35 GW) nuclear of 105 Gigawatt (GW) of installed capacity respectively, up from the 3 per cent (1830 MW) of Koeberg Nuclear Power Plant (Koeberg NPP). For the period 2041 – 2050, IRPs 6 and 7 have 6 per cent (7.56 GW) and 8 per cent (10.08 GW) nuclear of 126 GW of installed capacity respectively. The dissertation identifies the legal requirements and issues and makes recommendations on the steps to be followed to enable a legally sound nuclear rollout for SA.